Teaching effectiveness and course content suitability - a survey among KPLI English language trainees at the Kuala Terengganu Teacher Training College / Shamsudin Awang - Awang, Shamsudin (2009)
Using a sample of 102 trainee teachers from the Kuala Terengganu Teacher Training College, this study investigated the teaching effectiveness and the course content suitability pertaining to the KPLI English language program. As defined in Chapter 1, KPLI refers to a one-year postgraduate diploma in education course meant to train basic degree holders for the teaching career. The sample is randomly drawn from amongst those who are being trained to become English language teachers in Malaysian schools. The sample will be used to evaluate teaching effectiveness and course content suitability. In this study, the teaching effectiveness and course content suitability is considered adequate if its total score exceeds the midpoint value. Teaching effectiveness obtained a total mean score of 53.7 and the midpoint value was only 37.5. The total mean score obtained for course content suitability is nearly 60 while the midpoint value is 42.5. Thus in this study the teaching effectiveness and the course content suitability are largely considered adequate but the individual scores for variety of teaching aids and lecturer availability outside classroom hours was not very high. This implies that the relevant authorities need to give further thought to these areas. The study also found a strong positive correlation, (r = .699, p < 0.05) between teaching effectiveness and course content suitability indicating the mutual dependence of the two variables. A t-test was carried out to find out if the English majors and non-English majors scored differently for teaching effectiveness. A significant difference was found between the scores of the two groups implying that lecturers have to customize the pedagogy according to the background and option of the student. The sample was also divided into two age groups, 22 - 26 years and 27 - 35 years, '['-testing was also carried out to determine if this two age groups scored differently for teaching effectiveness and it was found that there was no significant difference between this two groups pertaining to the score for teaching effect.